A Comparative Performance Analysis of Two Printed Circular Arrays for Power-Based Vehicle Localization Applications - Mohammad S. Sharawi; Farooq Sultan; Daniel N. Aloi (International Journal of Antennas and Propagation)
A comparative study of the performance characteristics of a printed 8-element V-shaped circular antenna array and an 8-element Yagi circular array operating at 2.45 GHz for vehicular direction finding applications is presented. Two operating modes are investigated; switched and phased modes. The arrays were fabricated on FR-4 substrates with 0.8 mm thickness. Measured and simulated results were compared. Radiation gain patterns were measured on a 1 m diameter ground plane that resembles the rooftop of a vehicle. The HPBW of the Yagi was found to be about 3° narrower than its V-shaped counterpart when measured above a reflecting ground plane and operated in switched mode. The printed V-shaped antenna array offers 2.5 dB extra gain compared to the printed Yagi array.